Irrigated Corn Productivity as Influenced by Nitrogen Source, Rate, and Climatic Conditions. (1st November 2017) - Maharjan, Bijesh; Ferguson, Richard B.; Slater, Glen P.
Abstract : Core Ideas: Polymer coated N fertilizer was effective in improving crop yields. Chemical inhibitors used in the study was not effective in reducing environmental N losses. Varieties of available different chemical inhibitors may act differently and need to be compared and contrasted. Nitrogen fertilizer modifications such as coating or chemical additives are designed to either slow or inhibit N transformation, thereby to improve grain yield (GY) and reduce N losses. Effectiveness of these specialized products depend on various factors including climate. This field trial compared effects of various fertilizer modifications in irrigated corn ( Zea mays L.) in loamy sand in Nebraska. Urea–ammonia–nitrate (UAN), UAN with 30% methylene–urea (UAN–MU), split‐applied UAN‐MU (UAN–MU–SP) and polymer‐coated urea (PCU) were evaluated in 2009. In 2010 and 2011, UAN with nitrapyrin (UAN–IN) and nutrisphere (UAN‐NS) and PCU were evaluated. The PCU treatment consistently improved GY compared to other N treatments in all 3 yr irrespective of inter‐annual climatic variations. In 2009, a dry year, UAN–MU and UAN were not different but UAN–MU–SP increased GY, grain and total N uptake (GNU, TNU) compared to UAN and UAN–MU. In dry (2009) and wet (2011) years, residual N did not differ by N rate while it was the greatest in the highest N rate in 2010, a normal year. The UAN–IN and UAN–NS improved GY, GNU, and TNU compared to UAN in 2010. These treatments performed as well or better than UAN, even when the UAN rate was higher. In 2011 that had high potential for N leaching, UAN–IN and UAN–NS did not increase GY compared to UAN. In extreme weather conditions, chemical additives failed to improve performance of UAN, when N was all applied after corn emergence.